Economy: Exceptionality as a driver of structural change in the Basque Autonomous Community and Navarre - Juan Carlos Longas (Oñati Socio-Legal Series)
The global pandemic generated a crisis of still unpredictable consequences, further aggravated by the war in Ukraine. In 2008 a broad consensus had emerged on the need for far-reaching reforms, which basically meant doing away with the neoliberal consensus that had prevailed since the 1980s, although the chances of recovery were soon made dependent on the economic cycle. Once again, the current crisis is calling into question the quality and effectiveness of the social protection system and the welfare state itself. The responses seem to indicate a change of direction, towards safeguarding and strengthening the public sector. The Basque Country and Navarre are affected too. Two symptoms of this are the reinforcement of investment in health, which implies reversing previous cuts, and the approval of systems to cover the most disadvantaged groups. These measures require, however, the backing of other structural measures, particularly fiscal ones.